Establishment of soil strength in a nourished wetland using thin layer placement of dredged sediment. - Brian D Harris (Public Library of Science (PLoS), 2021)
Coastal wetlands are experiencing accelerated rates of fragmentation and degradation due to sea-level rise, sediment deficits, subsidence, and salt-water intrusion. This reduces their ability to provide ecosystem benefits, such as wave attenuation, habitat for migratory birds, and a sink for carbon and nitrogen cycles. A deteriorated back barrier wetland in New Jersey, USA was nourished through thin layer placement (TLP) of dredged sediment in 2016. A field investigation was conducted in 2019 using a cone penetrometer (CPT) to quantify the establishment of soil strength post sediment nourishment compared to adjacent reference sites in conjunction with traditional wetland performance measures. Results show that the nourished area exhibited weaker strengths than the reference sites, suggesting the root system of the vegetation is still establishing. The belowground biomass measurements correlated to the CPT strength measurements, demonstrating that shear strength measured from the cone penetrometer could serve as a surrogate to monitor wetland vegetation trajectories. In addition, heavily trafficked areas underwent compaction from heavy equipment loads, inhibiting the development of vegetation and highlighting how sensitive wetlands are to anthropogenic disturbances. As the need for more expansive wetland restoration projects grow, the CPT can provide rapid high-resolution measurements across large areas supplying government and management agencies with vital establishment trajectories.